2019
DOI: 10.1002/nbm.4103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MRI techniques to assess neonatal brain oxygenation and blood flow

Abstract: There is increasing interest in applying physiological MRI in neonates, based on the premise that physiological parameters may provide an early biomarker of neonatal brain health and injury. Two commonly used techniques are oxygen extraction fraction (OEF) measurement using T2‐relaxation‐under‐spin‐tagging (TRUST) MRI and cerebral blood flow measurement using phase‐contrast (PC) quantitative flow MRI, which collectively provide an assessment of the brain's oxygen consumption. However, prior research has only d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Neonatal cerebral MRI is challenging due to the small brain size and high susceptibility to motion. 15 Two noninvasive MRI techniques had been used in the included studies to estimate CBF without the application of contrast agents: phase contrast (PC) in eight studies and arterial spin labeling (ASL) sequences in six studies; one study combined both methods.…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal cerebral MRI is challenging due to the small brain size and high susceptibility to motion. 15 Two noninvasive MRI techniques had been used in the included studies to estimate CBF without the application of contrast agents: phase contrast (PC) in eight studies and arterial spin labeling (ASL) sequences in six studies; one study combined both methods.…”
Section: Resultsmentioning
confidence: 99%
“…200 Note that oxygen is delivered to the fetus from the placenta through the umbilical vein, which was reported to have an average oxygenation of 84%. 202 For newborn infants, several MRI techniques have been adapted to measure OEF in the neonatal brain, including T 2 -based 57,62,[203][204][205] and phase-based 206…”
Section: Oef Across the Human Lifespanmentioning
confidence: 99%
“…Adapted from Jiang et al 2 with permission global OEF of 31.8 ± 4.1%, which was similar to the adult OEF level. 204 There is currently a paucity of human studies on age-related OEF changes in children of 1 to 18 years of age. A previous 15 O-PET study found that OEF values in children were within the range of adult values regardless of the child's age.…”
Section: Oef Across the Human Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…The image quality challenge in advanced ioMRI acquisition with two RF coils arises from the limited scanning time during surgery, the relatively low signal‐to‐noise ratio (SNR) of advanced sequences, 4,5,15 and the restricted applicability of acceleration techniques, such as parallel imaging (e.g., SENSE) or Compressed Sensing, with a limited number of RF coils. Additional RF coils could impact image quality as they theoretically increase the geometry ( g ) factor and, consequently, SENSE's undersampling capabilities 16 .…”
Section: Introductionmentioning
confidence: 99%